Introduction to the theory of sustainable operation of technological systems for building reconstruction - Osipov, A.F. (Ways to Improve Construction Efficiency, 2023)
The article outlines the main provisions for increasing the stability of the functioning of technological systems in complex and changing conditions of reconstruction, accepted as a system of conceptual, theoretical, and methodological foundations for the formation of their morphological appearance as adaptive dynamically transforming technological systems. Increasing the stability of the functioning of technological systems in complex and dynamic conditions of reconstruction is ensured by the implementation of strategies: A-strategy. Reduced dynamics of environmental conditions; B-strategy. Ensuring an increased level of homeostasis of the technological system in relation to the external environment and the dynamics of its states. The A-strategy is implemented at the stages of preparation for reconstruction and in the process of its implementation, and the B-strategy is implemented by the formation of a technological system that ensures its invariance with respect to changes in the states of the external environment and which is carried out by increasing the functional inertia of the system, functional and structural redundancy. The author called such systems adaptive dynamically transforming technological systems. Adaptive dynamically transforming technological systems are endowed, on the one hand, with the properties of astatic systems – as systems with variable morphology, capable of detecting purposeful adaptive behaviour while maintaining internal balance, and, on the other hand, with the properties of static systems – as high-performance specialized systems with states. Astatic properties ensure optimization of costs for transforming the morphology and function of a technological system, as well as limiting system states to the minimum possible level, and static properties optimize differential effects on a variety of characteristic production situations. The use of adaptive dynamically transforming technological systems allows us to resolve the fundamental parametric contradiction in building reconstruction technology – highly efficient and sustainable implementation of non-stationary construction processes in complex and changing conditions of building reconstruction.